Analisis Kesulitan Belajar Bahasa Arab Mahasiswa Sekolah Tinggi Agama Islam Wakatobi - Daoed, Dessy Sintari; Lailaa, Hikmatul (CV. SINAR HOWUHOWU, 2025)
The main problem studied is students' low ability to understand and use Arabic, both actively and passively, which impacts their limited access to Islamic literature. The purpose of this study is to identify the types of difficulties in learning Arabic and analyze the causal factors, both internal (motivation, educational background, perception) and external (lecturer teaching methods and academic environment). This study employed a qualitative descriptive method, employing observation, in-depth interviews, and documentation analysis with students and lecturers in Arabic courses. The results indicate that the main difficulties faced by students lie in the application of grammar and grammatical rules, as well as poor speaking (kalam) and listening (istima') skills. This is caused by the dominance of the grammar-translation method and the limited language environment (bi'ah lughawiyyah). This study recommends changing the teaching approach to a communicative method and creating a conducive language environment on campus.